2018
DOI: 10.1111/jcmm.13739
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of competing endogenous RNA networks reveals the functional lncRNAs in heart failure

Abstract: Heart failure has become one of the top causes of death worldwide. It is increasing evidence that lncRNAs play important roles in the pathology processes of multiple cardiovascular diseases. Additionally, lncRNAs can function as ceRNAs by sponging miRNAs to affect the expression level of mRNAs, implicating in numerous biological processes. However, the functional roles and regulatory mechanisms of lncRNAs in heart failure are still unclear. In our study, we constructed a heart failure‐related lncRNA‐mRNA netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 44 publications
(83 reference statements)
0
27
0
1
Order By: Relevance
“…Emerging studies have suggested that ceRNAs exerted functions in certain disease or normal status (Shao et al, ). For example, Fan et al () constructed dysregulated ceRNA networks for heart failure and physiological condition and identified some key lncRNAs in the networks. Paci, Colombo, and Farina () built networks of miRNA‐mediated sponge interactions for healthy controls and breast cancer, which highlighted a marked rewiring in the ceRNA program between normal and disease status.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies have suggested that ceRNAs exerted functions in certain disease or normal status (Shao et al, ). For example, Fan et al () constructed dysregulated ceRNA networks for heart failure and physiological condition and identified some key lncRNAs in the networks. Paci, Colombo, and Farina () built networks of miRNA‐mediated sponge interactions for healthy controls and breast cancer, which highlighted a marked rewiring in the ceRNA program between normal and disease status.…”
Section: Discussionmentioning
confidence: 99%
“…Some ncRNAs-miRNAs-mRNAs networks were analyzed, leading to the discovery of numerous lncRNAs functional modules in heart failure [ 94 ] and in cardiac hypertrophy (CH), involving important oncogenic and well-characterized disease-related lncRNAs, such as HOX transcript antisense intergenic RNA (HOTAIR) [ 95 ] or myocardial infarction and associated transcript (MIAT) [ 96 , 97 ]. Specifically in CH, the crucial role of three new characterized lncRNAs (SLC26A4-AS1, RP11-344E13.3 and MAGI1-IT) was proven [ 98 ] by combining miRNA-transcript interactions, expression data of cardiac hypertrophy from an expressly re-annotated gene expression dataset, publicly available on Gene Expression Omnibus (GEO, a public functional genomics data repository), and an analysis of the most important network topological features like the degree, betweenness and closeness.…”
Section: Cerna and Diseasesmentioning
confidence: 99%
“…Manipulation of the expression of the Wisper, Meg3, and MIAT lncRNAs also affects cardiac fibrosis and pathological remodeling 47 49 . Tissue and plasma lncRNAs have been identified as potential biomarkers to predict the disease outcome for heart failure 32 , 50 52 . These studies highlight the therapeutic potential for lncRNA-targeted treatment for heart failure.…”
Section: Long Non-coding Rnasmentioning
confidence: 99%